Social media use and perceptions of physical health. Issue 1 (January 2019) - Dibb, Bridget
Abstract: Social networking activity is becoming more endemic in society and yet little is known about how the social comparison, occurring when we use these sites, affects perceptions of health. This study sought to determine in what way people who use Facebook (FB) interpret the comparison information they see on FB and whether this was associated with perceptions of physical health. Determining this association is important given the positive association between well-being, quality of life and physical health. Using a cross-sectional design, participants completed an electronic questionnaire measuring FB use, FB social comparison, self-esteem, depression, anxiety, life satisfaction and physical health. The data was analysed using Hierarchical Linear Regression to determine the association of social comparison on perceptions of physical health after controlling for other influencing factors. The results showed that participants were indeed socially comparing via FB. More positive upward comparison was reported, followed closely by positive downward and negative upward, with negative downward comparison perceived least. Analysis showed physical symptoms were associated with gender, anxiety, depression, FB use and positively interpreted upward comparison. Those who agreed more with the positively interpreted social comparison statements and who engaged more with FB also perceived more physical symptoms. These results showed that the perception of symptoms still occurred despite the positive comparison. These results have implications for perceptions of well-being for general users of FB and for vulnerable populations where more social comparison may occur.